Catalytic biofuel production over 3D macro-structured cheese-like Mn-promoted TiO2 isotype: Mn-catalyzed microwave-combustion design. (1st January 2022) - Bekhradinassab, Ensie; Tavakoli, Akram; Haghighi, Mohammad; Shabani, Maryam
Graphical abstract: Highlights: The 3D macro-structured cheese-like Mn-promoted TiO2 isotype was synthesized. The catalyst was fabricated via Mn-catalysed microwave-induced combustion. Microwave and Mn dopants had a potential effect in the enhancement of catalyst properties. Mn(4)Ti(MW) showed an effectual efficiency for biodiesel production from free fatty acids. A reaction pathway was proposed for the fabrication of 3D cheese like Mn-doped TiO2 . Abstract: The efficient 3D cheese like Mn-doped TiO2 catalyst was synthesized via Mn-catalyzed microwave-induced combustion for biodiesel production. The characterizations of Mn (0, 2, 4, and 6 at.%)-doped TiO2 were performed by XRD, FESEM, EDX, TEM, BET-BJH, and TPD-NH3 analyses. To compare the Mn (0 and 4 at.%)-doped TiO2 was also synthesized using muffle combustion. FESEM images and 3D surface analyses exhibited the cheese-like architecture assembled with nanosheets as well as by large uniform pores. Moreover, it showed that Mn played three significant roles. First, Mn promoted the rutile phase. Second, according to TPD-NH3 results, Mn dopant boosted acid sites, and acid density of catalyst as the number of acid sites was 35.534, and 42.777 µmol/g and acid density were 0.331, and 0.641 µmol/m 2 for undoped TiO2 and 4at. % Mn-doped TiO2, respectively. Third, Mn acted as a catalyzer in combustion reaction because Mn made the synthesis duration shorter, and consequently, the flow rate of exhaust gases increased (154.2 mol gas/min). Experimental results showed that biodiesel conversion was respectively about 42.8%, 62.6%, 72.8%, and 78.4% for Mn(0)Ti(MF), Mn(0)Ti(MW), Mn(0)Ti(MF), Mn(4)Ti(MW) during 2.5 h, indicating catalyst property promotion by Mn and its catalyzing role in combustion process. The selected Mn(4)Ti(MW) showed 89.1% conversion during 4 h, and conversion reduced only 1% after 6 successive runs.